L’expérimentation sociotechnique fondée sur les sciences comportementales : Un instrument au service de la production de l’acceptabilité sociale ? - Benoit Granier (VertigO)
Following its mobilisation by practitioners, the notion of social acceptability has been sparking interest and causing embarrassment among social scientists. This article contributes to the recent effort to clarify and question this notion, taking a national programme of socio-technical experimentation dedicated to smart grids in Japan as a case study. Although four “Smart Communities” have been designated, the peculiarity of this programme is the fact that the Japanese state is the initiator and supervisor of the experimentation. The latter is part of the state and private sector led strategy for producing the social acceptability of smart grids and their related products, equipments and services. This article analyses the concrete policy tools implemented, with a specific focus on the knowledge they are based upon. Smart Communities mobilise results from research in behavioural sciences (social psychology, behavioural economics) and marketing techniques in order to ensure the passive and active acceptance of users. The implementation of socio-technical experimentation allows for a hybrid way of producing social acceptability which is also part of a broader process of governmentalisation of practices that use energy which is paradoxically not based on ecological arguments.